2018
DOI: 10.20517/2394-5079.2018.29
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and hepatocarcinogenesis

Abstract: Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related deaths worldwide. There are two major challenges for HCC, the first being that early detection is generally not applicable, and secondly, it is usually fatal within several months after diagnosis. HCC is an inflammation-induced cancer. It is known that chronic inflammation leads to oxidative/nitrosative stress and lipid peroxidation, generating excess oxidative stress, together with aldehydes which can react with DNA bases to form pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 84 publications
2
49
0
Order By: Relevance
“…The same study revealed that the Keap1–Nrf2 (Kelch-like ECH-associated protein 1- Nrf2) system plays a central role in the protection of cells against oxidative and xenobiotic stresses [ 91 ]. Importantly, oxidative stress has emerged as a crucial player in HCC development and progression as 90% of HCC arise in the context of chronic liver inflammation, which leads to oxidative stress, generating excess reactive oxygen species (ROS) [ 92 , 93 ]. Nrf2-Keap1 system appeared also as an important metabolic regulator that redirects glucose and glutamine into the anabolic PPP in cancer cells [ 90 ].…”
Section: Rat Models Of Hccmentioning
confidence: 99%
“…The same study revealed that the Keap1–Nrf2 (Kelch-like ECH-associated protein 1- Nrf2) system plays a central role in the protection of cells against oxidative and xenobiotic stresses [ 91 ]. Importantly, oxidative stress has emerged as a crucial player in HCC development and progression as 90% of HCC arise in the context of chronic liver inflammation, which leads to oxidative stress, generating excess reactive oxygen species (ROS) [ 92 , 93 ]. Nrf2-Keap1 system appeared also as an important metabolic regulator that redirects glucose and glutamine into the anabolic PPP in cancer cells [ 90 ].…”
Section: Rat Models Of Hccmentioning
confidence: 99%
“…The latter findings are in line with previous reports in human samples and murine models. 53 We further performed a PCA analysis and confirmed that in liver and heart, α-dC composed a joint group with AST/ALT as a marker of liver injury and significantly correlated with each other in the NAFLD model. Importantly, we also confirmed higher levels of α-dC in the NRAS G12V /p19 Arf-/-HCC model.…”
Section: Discussionmentioning
confidence: 53%
“…When these mitochondrial abnormalities are accompanied by diminished intracellular antioxidant protection in NASH, pathways of fatty acid metabolism are altered [63] , which, in turn, can cause metabolic stress [63] . Overproduction of ROS frequently occurs in cancer, and is believed to play an important role in the development of HCC [64] . Intriguingly, oxidative stress and abnormal methylation of tumour suppressor genes are found the livers of NAFLD patients [65] .…”
Section: Metabolic Pathwaysmentioning
confidence: 99%